The project of creating psycho-artistic scenarios of modular-developmental interaction of the educational process participants - Sulyava, Olena (Psyhology & society, 2022)
The study was conducted in the context of segmental enrichment the theory and practice of the innovative system of modular-developmental education by A.V. Furman, who has thirty years of intellectual experience in epistemological formation and experimental confirmation of expediency and effectiveness. In particular, we are talking about the conceptual r e c o n s t r u c t i o n of a psycho-didactically competent and artistically oriented creation of educational scenarios of modular-developmental interaction between a teacher and students of general educational institution, presented in the form of a scientific project. First of all, based on the principle of logical-content complementarity, the basic parameters of the future interdisciplinary research are clearly recognized, namely the relevance of the topic, goal, tasks, object, subject, basic idea, hypothesis and methodological basis of the research. The main attention is focused around such an extremely complex object of psychodidactic cognition as the participants’ modular-developmental interaction of the organized educational process, which is technologically organized as a four-period and eight-stage cycle of parity educational deed of the mentor-psychologist and successors-subjects. Along with that, in this object, a localized subject field for detailed study has been mentally singled out – principles, regularities, compositional construction, forms, means and tools of psycho-artistic scripting as a separate professional thinking activity that in the innovative system of education follows the scientific design of educational modules and the construction of modular-developmental mini-textbooks. It has been programmatically underlined predicted author’s steps of the research from a comparative characteristic of the traditional plan-summary of a lesson and the educational scenario of modular lesson and attributive signs of the psycho-artistic course of the educational process to the peculiarities of confrontation of personal views and positions of educational cooperation participants, the vicissitudes of an organized educational action and to the wide functional-developmental possibilities of an educational scenario as a mature scientific-artistic product.